1973
DOI: 10.6017/ital.v6i2.5766
|View full text |Cite
|
Sign up to set email alerts
|

Catalog Records Retrieved by Personal Author Using Derived Search Keys

Abstract: <p class="p1">This investigation shows that search keys derived from personal a<span class="s1">u</span>thor names possess a sufficient degree of distinctness to be employed in an <span class="s2">effi</span>cient computerized interactive index to a <span class="s3">file </span>of MARC II catalog record<span class="s1">s </span>having 167,745 personal author entries.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…** Some of these searches could be successful done of the distribution of surname entries in replies retrieved from a database sample of books to ascertain that the average number of entries per reply will not be excessive. Landgraf & Kilgour(1973) provide a similar analysis for derived truncated keys.…”
Section: Reduction In Failure Due To Incorrect and Incomplete Author-mentioning
confidence: 79%
See 1 more Smart Citation
“…** Some of these searches could be successful done of the distribution of surname entries in replies retrieved from a database sample of books to ascertain that the average number of entries per reply will not be excessive. Landgraf & Kilgour(1973) provide a similar analysis for derived truncated keys.…”
Section: Reduction In Failure Due To Incorrect and Incomplete Author-mentioning
confidence: 79%
“…Online accesses will be analyzed for retrieval of author's name by single keyword, implied Boolean searches using two words in author or title or author and title, and derived truncated search keys, in the form of (4,1,) (Landgraf & Kilgour 1973). Keyword and Boolean searches require that words submitted for searching be correctly spelled.…”
Section: Reduction In Failure Due To Incorrect and Incomplete Author-mentioning
confidence: 99%
“…8 no. 3 Kilgour (6,7,8,9) and his associates at the Ohio College Library Center have used truncated keys derived from both personal author and titles in order to retrieve entries from a large on-line file of catalogue records. These keys were successful for the purpose they were designed for.…”
Section: Programmentioning
confidence: 99%
“…Record (entry) retrieval from large on-line catalogs has been intensively investigated (1)(2)(3)(4)(5)(6)(7), and the use of derived truncated search keys has proved in operation to be an effective method of retrieving entries from nametitle and title-only catalogs (5)(6)(7). The use of search keys derived from personal author and corporate author names for retrieval from on-line bibliographic files has also been studied (8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Landgraf er al. (8) conducted a similar investigation of the retrieval characteristics of corporate author search keys and concluded that the nature of corporate author names necessitates a different form of search key from that required by personal author names. These results were based on the number of records retrieved per search key.…”
Section: Introductionmentioning
confidence: 99%